Celiac Disease and Double-Balloon Enteroscopy: What Can We Achieve?. Issue 4 (April 2016) - Tomba, Carolina; Sidhu, Reena; Sanders, David S.; Mooney, Peter D.; Branchi, Federica; Locatelli, Martina; Roncoroni, Leda; Conte, Dario; Bardella, Maria T.; Elli, Luca
Abstract : Background: Indications to double-balloon enteroscopy (DBE) are not standardized in celiac disease (CD). Goals: To evaluate the clinical usefulness of DBE in complicated CD. Study: DBE findings in celiac patients with suspected small bowel (SB) complications were retrospectively evaluated in 2 tertiary referral centers (Milan and Sheffield). Demographic data of the studied cohort were compared with a database of 1000 noncomplicated CD patients. Results: Twenty-four CD cases (12 males, P =0.01 vs. controls) were reviewed. Mean age at CD diagnosis (y±SD) was 37±20 versus 27±18 and at SB evaluation 47±15 versus 38±13 ( P <0.01 compared with controls). Indications for DBE were refractory CD (#9), gastrointestinal symptoms (#6), severe iron-deficiency anemia (#6), and long standing poor dietary adherence (#3). Two jejunal adenocarcinomas and an ileal neuroendocrine tumor were detected in presence of iron-deficiency anemia. Three type I and 3 type II refractory CD patients showed jejunal ulcerations; 2 of type II presented small white raised patches. Patchy atrophy was observed in nonadherent patients and in 2 on a gluten-free diet for a short time. Therapy was planned in 33% of patients after DBE. No adverse events were detected at follow-up [21 mo (range, 0 to 60 mo)]. Conclusions: This is the largest international study on the outcomes of DBE in CD demonstrating its usefulness to exclude/confirm malignant or premalignant conditions, associated with even minor lesions. Studies are needed to understand the clinical relevance of the SB endoscopic features and to optimize DBE indications. Abstract : Supplemental Digital Content is available in the text.